2001
DOI: 10.1002/ijc.1394
|View full text |Cite
|
Sign up to set email alerts
|

p16INK4a Promoter hypermethylation of non-tumorous tissue adjacent to gastric cancer is correlated with glandular atrophy and chronic inflammation

Abstract: The p16INK4a tumor suppressor gene can be inactivated by promoter region hypermethylation in many tumor types including gastric cancers. However, p16INK4a promoter hypermethylation in the surrounding non-tumorous tissues of gastric cancers has not been studied in detail. We therefore examined 46 gastric cancers, corresponding adjacent nontumorous tissue samples and 8 gastric tissue samples of chronic gastritis by performing methylation-specific polymerase chain reaction, and we analyzed p16INK4a protein expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
36
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 19 publications
6
36
1
Order By: Relevance
“…Thus, methylation of p16 may play a role in the malignant transformation of gastric precursor lesions. The frequency of p16 methylation in adenocarcinoma in our study is similar to that reported in invasive gastric adenocarcinomas (Toyota et al, 1999b;Jang et al, 2001;Kang et al, 2001Kang et al, , 2003.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Thus, methylation of p16 may play a role in the malignant transformation of gastric precursor lesions. The frequency of p16 methylation in adenocarcinoma in our study is similar to that reported in invasive gastric adenocarcinomas (Toyota et al, 1999b;Jang et al, 2001;Kang et al, 2001Kang et al, , 2003.…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, however, we show that p16 gene methylation is present only in 7% of IM, but not in normal/CG mucosa, as has been reported previously (Jang et al, 2001;Kang et al, 2001).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The role of the pRb pathway in gastric carcinogenesis is the subject of many papers. In distal gastric cancers it may be that disruption of p16 is an early event [11] and a recent immunohistochemical study [12] has shown a progressive decrease in expression from gastritis to atrophy and dysplasia. Less information is available on the role of pRb expression.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] Aberrant methylation of p16 was reported to occur frequently in a variety of human cancers. 8 In GC, the frequency of p16 inactivation by methylation ranged from 32% to 67%, [9][10][11][12] whereas the frequencies by homozygous deletion and point mutation were both lower than 10%, [13][14][15] suggesting that methylation is a major mechanism for p16 inactivation in GC. Although p16 methylation in gastric precancerous lesions was reported, [16][17][18][19][20] however, the prevalence of aberrant p16 methylation in various gastric lesions was not reported on population-based study yet.…”
mentioning
confidence: 99%